As consequências da mineração de grande porte em Barro Alto, Goiás: desenvolvimento ou escambo contemporâneo? - Ribeiro, Renato de Araújo (2019)
The purpose of this dissertation is to investigate whether large-scale mining practiced by Transnational Corporations is a factor that induces local development or not. In order to do so, we opted for the investigation based on a case study focused on the reality of the Municipality of Barro Alto-GO. The research initially seeks to outline the context and historical importance of mining for the formation of the State of Goiás in order to describe how its economic, financial and social influence in the Municipality studied occurs. In order to answer the main question of this research, the collected data were submitted to the theoretical perspectives that approach the concept of development essentially as an economic data, establishing as signs of its existence the increase of productivity, Gross Domestic Product (GDP) per capita and real income, according to what Celso Furtado proposes. Also, as characterized by the creation of a synergic industrial sector with production of scale and scope, as proposed by, among others, Erik K. Reinert and Raúl Prebrish. Next, we analyze the local reality of the Municipality of Barro Alto from the perspective of the human rights to development, which we consider as the appropriate place or starting point for the correct understanding of the case studied. To do so, we rescued the historical construction of the human rights to development and we propose the interpretation of the real extension of its content from the point of view of Amartya Sen’s development theory, complemented by the conception that all rights demand a cost for its accomplishment, recognizing in the State and Transnational Corporations the main obliged ones to promote, defend and carry out, through planning and public policies, the human rights to development.